2011
DOI: 10.1111/j.1469-7580.2011.01429.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of light regimes and hormones on corneal growth in vivo and in organ culture

Abstract: Background When chicks are exposed to constant light during growth, their corneas become flatter and lighter in weight, and their anterior segments become shallower than those of chicks exposed to cyclical periods of light and dark. These effects have been correlated with constant light suppression of cyclical changes in melatonin levels. The question of whether light directly influences corneal growth (e.g. via cryptochromes in the cornea) or whether it acts remotely via the suppression of the melatonin rhyth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…While our results show an association between refractive status and serum Mel, our data cannot be used to indicate a causal relationship. Our findings align with animal models of experimentally induced myopia in which systemic and ocular application of Mel has been shown to impact on refractive status and ocular shape and suggest that Mel may influence human refractive error and ocular shape . Further research is required to determine the nature of this influence.…”
Section: Discussionsupporting
confidence: 76%
“…While our results show an association between refractive status and serum Mel, our data cannot be used to indicate a causal relationship. Our findings align with animal models of experimentally induced myopia in which systemic and ocular application of Mel has been shown to impact on refractive status and ocular shape and suggest that Mel may influence human refractive error and ocular shape . Further research is required to determine the nature of this influence.…”
Section: Discussionsupporting
confidence: 76%
“…This was hypothesized to be due to maintenance of normal melatonin secretion rhythms in hooded chicks. Additionally, Wahl et al (2011) demonstrated that giving daily melatonin eye drops to CL chicks was protective against development of hyperopia. Additionally, they found that administering a melatonin hormone blocker, luzidone, caused normal day-night cycle chicks to develop hyperopia.…”
Section: Current Research Applications: Chick Models For Human Dismentioning
confidence: 99%
“…When CL chicks are treated with melatonin eye drops during the subjective night, the eye is protected and grows normally. Conversely, when chicks in normal day/night cycles are treated with the melatonin receptor antagonist luzindole, they develop hyperopia (Li & Howland, 2002; Wahl, Li, Takagi & Howland, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…While these rhythms have not been established as important factors in normal ocular growth, their absence, correlated with abnormalities in ocular growth, is suggestive. Moreover, when melatonin rhythms are blocked in chicks raised in N conditions, they develop hyperopia (Li & Howland, 2002; Wahl, Li, Takagi & Howland, 2011). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation